2006
DOI: 10.1143/jjap.45.5344
|View full text |Cite
|
Sign up to set email alerts
|

One-Way Quantum Key Distribution System Based on Planar Lightwave Circuits

Abstract: We developed a one-way quantum key distribution (QKD) system based upon a planar lightwave circuit (PLC) interferometer. This interferometer is expected to be free from the backscattering inherent in commercially available two-way QKD systems and phase drift without active compensation. A key distribution experiment with spools of standard telecom fiber showed that the bit error rate was as low as 6% for a 100-km key distribution using an attenuated laser pulse with a mean photon number of 0.1 and was determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…These results suggest that our PLC-based interferometer allows us to implement a QKD system insensitive to polarization effects that may occur in the transmission fiber, since the same balancing condition is sufficient to achieve polarization insensitivity [38]. The polarization-insensitive operation of a time-division interferometer based on our PLC AMZI has actually been proven by the authors using the experimental setup shown in Figure 7 [35,36]. Two PLC AMZIs and a polarization scrambler were connected in series using a single-mode fiber patch cable, and relatively intense optical pulses were introduced into the first AMZI.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…These results suggest that our PLC-based interferometer allows us to implement a QKD system insensitive to polarization effects that may occur in the transmission fiber, since the same balancing condition is sufficient to achieve polarization insensitivity [38]. The polarization-insensitive operation of a time-division interferometer based on our PLC AMZI has actually been proven by the authors using the experimental setup shown in Figure 7 [35,36]. Two PLC AMZIs and a polarization scrambler were connected in series using a single-mode fiber patch cable, and relatively intense optical pulses were introduced into the first AMZI.…”
supporting
confidence: 56%
“…The key to our proposal is the use of planar lightwave circuit (PLC) technology [32][33][34][35][36], which enables us to implement a reliable interferometric optical system that is robust to change in ambient conditions [37]. By using PLC technology, we developed compact and easy-to-use passive interferometric devices to manipulate a photonic time-bin qubit with increased stability, reliability, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interferometers made of low thermal factor materials [13] or integrated planar silica waveguide with thermal and mechanical isolation can be used in passive compensation [14,15] . Another improved way to passively compensate for phase drift is to find the environment temperature of interferometers, at which the difference between the modal phase shifts in the long and short arms of the AMZI (ș L ș S ) is multiples of 2ʌ [16] . Although these measures can suppress the harmful temperature disturbance of environment, there must be accurate temperature controller with precision of 0.01 in the system.…”
Section: Quantum Informationmentioning
confidence: 99%
“…An experimental metropolitan-area QKD network has been developed and deployed in the Boston area [18], and similar efforts are underway in Japan [19] and Europe [20]. Efforts to extend these networks to wider areas are constrained by loss in the communication channel, which results in exponential decay in throughput as distance increases.…”
Section: Introductionmentioning
confidence: 99%